The generalized sampling theorem for transforms of not necessarily square integrable functions - A. J. Jerri (International Journal of Mathematics and Mathematical Sciences)
It is known that the generalized sampling theorem is valid for certain finite limit integral transforms of square integrable functions. In this note, we will extend the validity of the theorem to include transforms of absolutely integrable functions associated with differentiable kernels. In the proof, we will use the Hölder inequality and a known theorem concerning the uniform convergence of the orthogonal series to the differentiable kernel of the particular integral transform.